Digital Literation of Micro, Small and Medium Enterprises (MSMEs) in Jember District. Issue 1 (May 2021) - Islami, N N; Wahyuni, S; Puji, R P N
Abstract: This study aims to find out how: a) ownership of digital facilities, the ability to access and the ability to use digital media, b) opportunities to access media both social media and other internet networked media, c) use of digital media to support efforts to sustain the productive business of business actors. Micro, Small, and Medium Enterprises in Jember Regency. The qualitative descriptive research method uses data collection techniques using interviews, observation, and documentation to obtain information, to answer the problems formulated, and the objectives to be achieved. The results showed that: 1) as many as 67% of MSMEs actors in Jember did not have digital media facilities in the form of computers, but other findings showed that 73% of MSMEs players had experience in using computers. This shows that even though they do not have computer facilities, some MSMEs players still have experience in using computers, meaning that some of the MSMEs players who have limited ownership of digital facilities are still trying to keep learning in the use of digital media. Based on the results of the interview, they admitted that they often borrow computers from relatives and friends to study mainly related to product design and marketing. They do this if they have trouble using only their cellphones. Meanwhile, the frequency of MSMEs players using computers in the past week was 7% more than 6 times, 13% 3-6 times, 20% 1-3 times, and 60% did not use computers at all. 7% of MSMEs players who frequently use computers in the past week explained that they do have promotional media on several marketplaces, social media and also own the web. So, every day they have to use computers to serve consumers as a routine activity, this is felt to make it easier for them to carry out online marketing and learn applications that can support product quality improvement when compared to using cellphones. Based on the findings in this research, it shows that the frequency of use of digital media for business development and increasing literacy of MSMEs actors in Jember Regency is still in the low category. 2) The dominant media facilities used for accessing the internet are cellphones at 67%, PCs at 33%, and internet cafes at 0%. Meanwhile, the dominant media channel they access is social media, namely 73% of which they tend to access are Facebook, IG, WA. On average, the respondents are not familiar with other social media besides those social media. Then for access to the marketplace by 13%, email access is only 7%. Based on these findings, it can be seen that most of the MSMEs players in Jember have not used other media such as market places, market space, and email. The use of email is only a condition for opening social media. Meanwhile, about the objectives of MSMEs players in accessing information, 67% of the objectives of accessing information were for product marketing, 13% were looking for information related to product development and business development, 7% were looking for information about competitors, and 13% for other activities. that has nothing to do with effort. 3) Efforts to sustain the productive businesses of MSMEs players in the district. Jember has been running and going on from year to year. However, most of the MSMEs actors are still unable to carry out managerial management ideally. There are still many MSMEs that have not been able to take advantage of opportunities in the current digital era. For MSMEs that are already able to take advantage of digital media in helping their business management, including marketing management, finance, information, and others, it can accelerate the pace of development and business sustainability.